2019
DOI: 10.3389/fcvm.2019.00127
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Genetics Update: Toward Clinical Implementation

Abstract: Atrial fibrillation (AF) is the most common heart rhythm disorder worldwide and may have serious cardiovascular health consequences. AF is associated with increased risk of stroke, dementia, heart failure, and death. There are several known robust, clinical risk predictors for AF, such as male sex, increasing age, and hypertension; however, during the last couple of decades, a substantive genetic component has also been established. Over the last 10 years, the discovery of novel AF-related genetic variants has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 141 publications
0
11
0
Order By: Relevance
“…Atrial fibrillation (AF) is caused by various mechanisms and one of the most common cardiac rhythm disturbances (Chua et al, 2019;Sutanto et al, 2019) associated with increased risk of heart failure, stroke (Kostopoulou et al, 2019), and death. More than dozens of genetic loci have been associated with AF, but the current review does not attempt to focus on these genetic mechanisms (Kalsto et al, 2019) and clinical management (Sutanto et al, 2019) of AF in detail.…”
Section: The Heart and Arrhythmiasmentioning
confidence: 99%
“…Atrial fibrillation (AF) is caused by various mechanisms and one of the most common cardiac rhythm disturbances (Chua et al, 2019;Sutanto et al, 2019) associated with increased risk of heart failure, stroke (Kostopoulou et al, 2019), and death. More than dozens of genetic loci have been associated with AF, but the current review does not attempt to focus on these genetic mechanisms (Kalsto et al, 2019) and clinical management (Sutanto et al, 2019) of AF in detail.…”
Section: The Heart and Arrhythmiasmentioning
confidence: 99%
“…The diamond represents the OR and 95% CI of the pooled results. (24,25). Given more and more published studies with inconclusive results, our current study may provide some insight into further clarification of the relationship between rs13216675 and risk of AF and may direct future research to potential targets of prevention, treatment, and management of AF.…”
Section: Discussionmentioning
confidence: 83%
“…The occurrence of AF and CS can be reduced by treatment by those measures for T2D patients. However, as far as the early prevention and control of AF and CS are concerned, clinical evaluation of genetic risk is an important link in comprehensive management of AF in diabetes that cannot be ignored [ 21 ]. Like diabetes, recent genetic studies indicated that there is also an obvious genetic predisposition for the occurrence of AF [ 22 ].…”
Section: Discussionmentioning
confidence: 99%